Culture and Motivation: The Globalised Learning Paradigm from a Regional Perspective - Randeree, K; Randeree, M (Common Ground Publishing, 2009)
The United Arab Emirates (UAE) is one of the most diverse nations in the world, with over one hundred nationalities living in an area no larger than the US state of Texas. In such an envorinment, where citizens amount to only one fifth of the country’s population, supported by an expatriate population with an assortment of cultures, the development of a university education system to accommodate the needs of the inhabitants could never be ‘one-size-fits-all.’ This paper explores the influence of globalisation on higher education and its impact on citizens of the United Arab Emirates. The paper further investigates the challenges they face in learning in English, a second language to them; motivational problems ensuing from experiencing a paradigm shift in the classroom; cultural challenges they experience in, for example, having to learn from imported textbooks resulting in difficulty in content contextualisation; dealing with differences in values and morals, between, for example, foreign educators and indigenous students.